Perancangan Sistem Manajemen dan Monitoring Switch DCN S4600 -10P-SI Berbasis Web - Saputra, Yogi; Septanto, Henri (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2025)
Monitoring in a network is an activity in managing a network system on a server. The application of a web-based network management and monitoring switch system is very much needed to facilitate and provide more benefits for a monitor in carrying out his duties in monitoring each device that is directly connected to the internet network that is spread across various predetermined areas. In addition to being used in network monitoring activities, this application can also provide advantages in providing information about the signal power that can be received from a switch device that is directly connected to the server via a Fiber Optic cable transmission media. The signal power received on the switch device can affect the quality of the internet network used by users in that area. In addition, this monitoring application is also used in recording active device assets installed in various installed areas. So with this switch management and monitoring application, it can provide more benefits to the monitoring team in monitoring the internet network on all switch devices spread across various predetermined areas.